Scaphosepalum zieglerae, a showy new species in the genus (Pleurothallidinae: Orchidaceae) - Baquero R., Luis E. (Lankesteriana: International Journal on Orchidology, 2017)
Scaphosepalum zieglerae is described from a small area near Chical in northern Ecuador. It is distinguished by the large plant, waxy yellow flowers densely spotted with brown red to blood-red, spiky tails of the lateral sepals and a dark blood-red, wingless lip. It is here compared to Scaphosepalum beluosum with which it shares most similarities, and to S. fimbriatum, another species with fimbriated sepaline tails.